Exploring the Pattern of Happiness in Indonesia Based on Public Green Spaces - Aprildahani, Baiq Rindang; Kurnianingsih, Nela Agustin; Hutama, Surya Tri Esthi Wira; Permana, Chrisna Trie Hadi (Jurnal Planologi, 2025)
ABSTRACTHappiness may be one of the most important pillars of life for people. The recent Indonesia’s happiness index has been measured by The Indonesia’s National Statistics Bureau (BPS) in 2021. The happiness index is composed by 19 indicators, which grouped into 3 dimensions, namely the dimensions of life satisfaction, feelings, and meaning of life. However, the presence of green spaces is not related to one of them. Meanwhile, there are three broad areas of research on happy cities: social determinants of well-being, economic determinants of well-being, and environmental determinants of well-being. One of the environmental determinants of well-being is the presence of green spaces. Many studies have shown that people who live in areas with more green spaces have less stress and emotional pressure, as well as a greater sense of happiness and satisfaction. This study aims to examine the relationship between the happiness index and the amount of public green spaces in Indonesia even though the happiness index measurement does not involve green spaces indicators. This study contributes by integrating spatial analysis with subjective well-being metrics in Indonesia’s urban policy context. The method used is simple linear regression analysis to determine the direction of influence and its magnitude. Data and information were collected from secondary sources. The results show that the area of public green spaces has positive effect to the happiness index even in Indonesia. It is suggest the need for integrating green infrastructure in happiness indicators and spatial planning programs.Keywords: Happy City, Urban Happiness, Green Spaces, Happiness Index, Indonesia ABSTRAKKebahagiaan mungkin merupakan salah satu pilar terpenting dalam hidup manusia. Indeks kebahagiaan Indonesia yang terbaru diukur oleh Badan Pusat Statistik (BPS) pada tahun 2021. Indeks kebahagiaan disusun berdasarkan 19 indikator yang dikelompokkan ke dalam 3 dimensi, yaitu dimensi kepuasan hidup, perasaan, dan makna hidup. Namun, keberadaan ruang terbuka hijau tidak terkait dengan salah satunya. Sementara itu, ada tiga area besar penelitian tentang kota bahagia: determinan sosial dari kesejahteraan, determinan ekonomi dari kesejahteraan, dan determinan lingkungan dari kesejahteraan. Salah satu faktor lingkungan yang memengaruhi kesejahteraan adalah keberadaan ruang hijau. Banyak penelitian telah menunjukkan bahwa orang yang tinggal di daerah dengan lebih banyak ruang hijau memiliki lebih sedikit stres dan tekanan emosional, serta rasa bahagia dan kepuasan yang lebih besar. Penelitian ini bertujuan untuk mengetahui apakah hasil indeks kebahagiaan yang diukur oleh BPS Indonesia berhubungan dengan keberadaan RTH meskipun pengukuran indeks kebahagiaan tidak melibatkan indikator RTH. Studi ini memberikan kontribusi dengan mengintegrasikan analisis spasial dengan indikator kebahagiaan yang subjektif dalam konteks kebijakan perkotaan di Indonesia. Metode yang digunakan adalah analisis regresi linier sederhana untuk mengetahui arah pengaruh dan besarannya. Data dan informasi dikumpulkan dari sumber sekunder. Hasil penelitian menunjukkan bahwa memang benar luas RTH publik berpengaruh terhadap indeks kebahagiaan bahkan di Indonesia dan berpengaruh positif. Oalh karena itu, disarankan untuk mengintegrasikan infrastruktur hijau ke dalam indikator pengukuran kebahagiaan dan program perencanaan ruang.Kata kunci: Kota Bahagia, Ruang Terbuka Hijau, Indeks Kebahagiaan, Indonesia